Increased bystander intervention when volunteer responders attend out-of-hospital cardiac arrest - Nielsen, Christian Gantzel; Folke, Fredrik; Andelius, Linn; Hansen, Carolina Malta; Væggemose, Ulla; Christensen, Erika Frischknecht; Torp-Pedersen, Christian; Ersbøll, Annette Kjær; Gregers, Mads Christian Tofte (Frontiers in Cardiovascular Medicine, 2022)
Aim The primary aim was to investigate the association between alarm acceptance compared to no-acceptance by volunteer responders, bystander intervention, and survival in out-of-hospital cardiac arrest. Materials and methods This retrospective observational study included all suspected out-of-hospital cardiac arrests (OHCAs) with activation of volunteer responders in the Capital Region of Denmark (1 November 2018 to 14 May 2019), the Central Denmark Region (1 November 2018 to 31 December 2020), and the Northern Denmark Region (14 February 2020 to 31 December 2020). All OHCAs unwitnessed by Emergency Medical Services (EMS) were analyzed on the basis on alarm acceptance and arrival before EMS. The primary outcomes were bystander cardio-pulmonary resuscitation (CPR), bystander defibrillation and secondary outcome was 30-day survival. A questionnaire sent to all volunteer responders was used with respect to their arrival status. Results We identified 1,877 OHCAs with volunteer responder activation eligible for inclusion and 1,725 (91.9%) of these had at least one volunteer responder accepting the alarm (accepted). Of these, 1,355 (79%) reported arrival status whereof 883 (65%) arrived before EMS. When volunteer responders accepted the alarm and arrived before EMS, we found increased proportions and adjusted odds ratio for bystander CPR {94 vs. 83%, 4.31 [95% CI (2.43–7.67)] and bystander defibrillation [13 vs. 9%, 3.16 (1.60–6.25)]} compared to cases where no volunteer responders accepted the alarm. Conclusion We observed a fourfold increased odds ratio for bystander CPR and a threefold increased odds ratio for bystander defibrillation when volunteer responders accepted the alarm and arrived before EMS.